PENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR MATEMATIKA SISWA KELAS 8 A MTS NEGERI 1 PATI MELALUI PEMBELAJARAN DENGAN MEDIA GEOGEBRA - Mohamad Salim (JIEBAR : Journal of Islamic Education: Basic and Applied Research, 2022)
Classroom action research in general aims to improve the quality of learning of 8th grade MTs N 1 Pati learners. Research is carried out in two cycles, where each cycle consists of planning, implementation, observation, and reflection stages. Cycle I and cycle 2 each consist of two encounters. Student activity data is dug up with a Learner's Liveliness Observation Sheet, while the student's learning outcome data is dug up with the Learning Outcome Test. This research includes a type of classroom action research (PTK), with its main characteristic being repeated actions and the main method is self-reflection aimed at improving learning. PTK is a problem-solving activity characterized by cyclic and reflection that starts from: a) planning, b) actions, c) observing, d) analyzing data/information to decide the extent of the advantages and disadvantages of such actions (reflecting). PTK is characterized by continuous improvement so that research satisfaction is often the benchmark of the cycle. The use of the right media in mathematics learning will be able to change students' attitudes and behaviors to be more active in participating in mathematics lessons while making it easier for students to find their own problem solving results. In this case the medium used is Geogebra to help explain the material of the Circle. The results of the study turned out that with geogebra media can increase the activeness and learning outcomes of students. This can be seen from the percentage increase in the results of observations of activeness learning from all aspects from pre-cycle to cycle 2 experienced an increase of 32.45% and the increase in the average score of the replay value from the initial condition to cycle 2 increased by 19.65%.